The science of puromycin: From studies of ribosome function to applications in biotechnology - Ranen Aviner (Computational and Structural Biotechnology Journal, 2020)
Puromycin is a naturally occurring aminonucleoside antibiotic that inhibits protein synthesis by ribosome-catalyzed incorporation into the C-terminus of elongating nascent chains, blocking further extension and resulting in premature termination of translation. It is most commonly known as a selection marker for cell lines genetically engineered to express a resistance transgene, but its additional uses as a probe for protein synthesis have proven invaluable across a wide variety of model systems, ranging from purified ribosomes and cell-free translation to intact cultured cells and whole animals. Puromycin is comprised of a nucleoside covalently bound to an amino acid, mimicking the 3′ end of aminoacylated tRNAs that participate in delivery of amino acids to elongating ribosomes. Both moieties can tolerate some chemical substitutions and modifications without significant loss of activity, generating a diverse toolbox of puromycin-based reagents with added functionality, such as biotin for affinity purification or fluorophores for fluorescent microscopy detection. These reagents, as well as anti-puromycin antibodies, have played a pivotal role in advancing our understanding of the regulation and dysregulation of protein synthesis in normal and pathological processes, including immune response and neurological function. This manuscript reviews the current state of puromycin-based research, including structure and mechanism of action, relevant derivatives, use in advanced methodologies and some of the major insights generated using such techniques both in the lab and the clinic.